Malware detection in macOS using supervised learning - BURGARDT, Caio Augusto Pereira (2022)
The development of macOS malware has grown significantly in recent years. Attackers have become more sophisticated and more targeted with the emergence of new dangerous malware families for macOS. However, since the malware detection problem is very dependent on the platform, solutions previously proposed for other operating systems cannot be directly used in macOS. Malware detection is one of the main pillars of endpoint security. Unfortunately, there are very few works on macOS endpoint security, which is considered a largely unexplored territory. Currently, the only malware detection mechanism in macOS is a signature-based system with less than 200 rules as of 2021, called XProtect. Recent works that attempted to improve the detection of malwares in macOS have methodology limitations, such as the lack of a large macOS malware dataset and issues that arise with imbalanced datasets. In this work, we bring the malware detection issue to the macOS operating system and evaluate how supervised machine learning algorithms can be used to improve endpoint security in the macOS ecosystem. We create a new and larger dataset of 631 malware and 10,141 benign software using public sources and extracting information from the Mach-O format. We evaluate the performance of seven different machine learning algorithms, two sampling strategies and four feature reduction techniques in the detection of malwares in macOS. As a result, we present models that are better than macOS native protections, with detection rates larger than 90% while maintaining a false alarm rate of less than 1%. The presented models successfully demonstrate that macOS security can be improved by using static characteristics of native executables in combination with common machine learning algorithms.